1-MCP Application affects ethylene production, storage life and quality of `Tegan Blue' plum - Khan, Ahmad; Singh, Zora (Interntional Society Horticultural Science, 2008)
Postharvest fruit softening is a major factor limiting shelf life of plum. Ethylene plays an important role in softening of plum fruit during ripening and storage. 1-MCP application has been reported to maintain plum fruit firmness in the postharvest phase. No information is available on the influence of 1-MCP on plum fruit quality parameters (total carotenoids, vitamin C and total antioxidants) during ripening and in stored fruit. The aim of this study was to elucidate the effects of postharvest application of 1-MCP on ethylene production, fruit quality during ripening and after three or six weeks of storage. In the first experiment plum (Prunus salicina L. ‘Tegan Blue’) fruit were treated with 1-MCP (0, 0.5, 1.0 or 2.0 μl·L-1) at 20±1°C for 24 h and allowed to ripen at ambient temperature (20±1°C). In the second experiment, following the 1-MCP (0, 0.5, 1.0 or 2.0 μl·L-1) application at 20±1°C for 24 h, fruit werestored at 0±1°C and 90 ± 5% RH for three or six weeks. In both experiments, 1-MCP application significantly delayed and suppressed the climacteric ethylene production and respiration rate. In the first experiment, during ripening, treated fruit maintained a higher fruit firmness, acidity, L*, a*, b*, chroma values and hue angle while their soluble solid content (SSC), vitamin C and total antioxidants were lower than the control. In the second experiment, 1-MCP treated fruit maintained higher fruit firmness, acidity and chroma values while lower levels of SSC, total carotenoids, vitamin C and total antioxidants were measured in the treated fruit. In conclusion, 1-MCP (1.0 μl·L-1) can be used effectively to suppress and delay the climacteric ethylene production with acceptable quality during ripening at ambient temperature and with the same treatment plum storage life can be extended up to six weeks with minimum losses of fruit quality.